A single N‐terminal phosphomimic disrupts TDP‐43 polymerization, phase separation, and RNA splicing. (9th February 2018) - Wang, Ailin; Conicella, Alexander E; Schmidt, Hermann Broder; Martin, Erik W; Rhoads, Shannon N; Reeb, Ashley N; Nourse, Amanda; Ramirez Montero, Daniel; Ryan, Veronica H; Rohatgi, Rajat; Shewmaker, Frank; Naik, Mandar T; et al.
Abstract: TDP‐43 is an RNA‐binding protein active in splicing that concentrates into membraneless ribonucleoprotein granules and forms aggregates in amyotrophic lateral sclerosis (ALS) and Alzheimer's disease. Although best known for its predominantly disordered C‐terminal domain which mediates ALS inclusions, TDP‐43 has a globular N‐terminal domain (NTD). Here, we show that TDP‐43 NTD assembles into head‐to‐tail linear chains and that phosphomimetic substitution at S48 disrupts TDP‐43 polymeric assembly, discourages liquid–liquid phase separation (LLPS) in vitro, fluidizes liquid–liquid phase separated nuclear TDP‐43 reporter constructs in cells, and disrupts RNA splicing activity. Finally, we present the solution NMR structure of a head‐to‐tail NTD dimer comprised of two engineered variants that allow saturation of the native polymerization interface while disrupting higher‐order polymerization. These data provide structural detail for the established mechanistic role of the well‐folded TDP‐43 NTD in splicing and link this function to LLPS. In addition, the fusion‐tag solubilized, recombinant form of TDP‐43 full‐length protein developed here will enable future phase separation and in vitro biochemical assays on TDP‐43 function and interactions that have been hampered in the past by TDP‐43 aggregation. Synopsis: The N‐terminal globular domain (NTD) of TDP‐43 forms linear polymers whose disruption by phosphomimetic substitution reduces TDP‐43 liquid‐liquid phase separation and RNA splicing function. TDP‐43 NTD polymerization is disrupted by the phosphomimetic substitution at S48. NTD forms a linear polymer through low‐affinity head‐to‐tail intermolecular contacts. TDP‐43 NTD polymerization‐disrupting mutations destabilize phase separation of full‐length TDP‐43 in vitro and in cells. Disrupting NTD polymerization impedes TDP‐43's role in RNA splicing in cells. Abstract : Structural and functional analyses of ALS‐related protein TDP43 illustrates its higher order organisation and links splicing activity with the ability to undergo liquid–liquid phase separation.